Water-based ester-based coated urea fertilizer, preparation method and application

By forming an aqueous ester-based envelope on the surface of urea particles, using materials such as polyvinyl alcohol, citric acid, corn stalk and ethyl cellulose, the problems of water resistance and poor sustained release of existing enveloped sustained release fertilizers are solved, and efficient and economical fertilizer sustained release effect is achieved.

CN119841683APending Publication Date: 2025-04-18TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510119981.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing enveloped sustained-release fertilizers have poor performance in water resistance and sustained-release properties, and the large amount of coating alone leads to high costs.

Method used

Using aqueous ester-based envelope material, polyvinyl alcohol is mixed with citric acid and corn stalks to form an inner membrane solution, and mixed with ethyl cellulose and glycerol to form an outer membrane solution, and a double-layer film is formed on the surface of urea particles by spraying technology.

Benefits of technology

It improves the water resistance, mechanical properties and sustained release properties of the envelope materials, reduces the preparation cost of the envelope fertilizer, realizes efficient and comprehensive utilization of resources, and provides a continuous and balanced nutrient supply to crops.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841683A_ABST
    Figure CN119841683A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based ester-based coated urea fertilizer, a preparation method and application. The preparation method comprises the following steps: mixing citric acid and a polyvinyl alcohol solution, adding corn straw powder, and stirring to form an inner membrane solution; adding glycerol into the ethyl cellulose ethanol solution, and stirring to obtain an outer membrane solution; the urea particles are put into a coating machine to be preheated and polished, the inner film solution is sprayed to the surfaces of the urea particles to form coating layers, and the single-inner-film coated urea particles are obtained; and then spraying the outer film solution on the surface of the single inner film coated urea particle for the second time to obtain the double-layer film urea particle. The citric acid and the corn straw are mixed with the polyvinyl alcohol, so that the mechanical property, the hydrophobic property and the thermal stability of the polyvinyl alcohol coating material are improved; ethyl cellulose plasticized by glycerol is enhanced in hydrophobicity, stable in mechanical structure and free of biological toxicity, and can effectively protect the fertilizer and greatly reduce the release speed of the fertilizer as an outer protective layer of the coated fertilizer, so that continuous and balanced nutrient supply is provided for crops.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fertilizer preparation methods, and in particular relates to an aqueous ester-coated urea fertilizer, and also relates to a preparation method and application of the aqueous ester-coated urea fertilizer. Background Art

[0002] Fertilizer is a key element in the agricultural production process and has made great contributions to the high yield and quality of crops. However, the use of traditional fertilizers will lead to problems such as unstable fertilizer effect, serious nutrient loss, groundwater pollution and excessive greenhouse gas emissions. The emergence of slow-release fertilizers provides an effective way to solve these problems. Slow-release fertilizers slow down the release of fertilizers through various methods to improve the efficiency of nutrient absorption and utilization of crops.

[0003] Coated slow-release fertilizers are developing most rapidly in the field of slow-release fertilizers, and their applications are becoming more and more extensive. Among them, organic coating materials improve the strength and brittleness of the film layer on the basis of inorganic coating materials, and have good controlled release function, which can significantly improve the utilization efficiency of fertilizers. Polyvinyl alcohol is non-toxic and harmless, and is one of the known coating materials that can be degraded by environmental microorganisms, but the water resistance and slow-release performance of pure polyvinyl alcohol film materials are not ideal. The film structure prepared by ethyl cellulose is stable, and studies have shown that it has no toxic effects on organisms and the environment. Although coating it on the surface of fertilizers will reduce the release rate of fertilizers to a certain extent, there is still room for optimization and improvement, and the large amount used when coating alone leads to high costs. How to modify polyvinyl alcohol and ethyl cellulose, and how to optimize the spatial structure combination with urea to obtain a new type of slow-release nitrogen fertilizer needs to be solved and explored. Summary of the invention

[0004] The present invention also aims to provide a method for preparing an aqueous ester-coated urea fertilizer, thereby solving the problems of poor water resistance and slow release of existing coated slow-release fertilizers.

[0005] Another object of the present invention is to provide an aqueous ester-based coated urea fertilizer.

[0006] The present invention also aims to provide the application of the aqueous ester-based coated urea fertilizer.

[0007] The first technical solution adopted by the present invention is: a method for preparing water-based ester-coated urea fertilizer, and the specific operating steps are as follows: Step 1: Mix polyvinyl alcohol and deionized water, stir with a magnetic stirrer, and heat to 95° C. until the polyvinyl alcohol is completely dissolved; cool the polyvinyl alcohol solution, add citric acid, and stir at a constant temperature; after complete mixing, add corn stalk powder and stir to obtain an aqueous ester-based polymer solution, i.e., an inner membrane solution; Step 2: adding ethyl cellulose to anhydrous ethanol and stirring until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution, and adding glycerol to the ethyl cellulose ethanol solution and stirring to obtain an outer membrane solution; Step 3: Place the urea granules in a water chestnut-type coating machine for preheating and polishing, then adjust the coating temperature to 55-75°C, use a spray gun connected to an air compressor to spray the prepared inner film solution onto the surface of the urea granules to form a coating layer, and keep the temperature after spraying to obtain single inner film coated urea granules; Step 4: Then, the outer membrane solution described in step 2 is sprayed twice on the surface of the single inner membrane coated urea particles described in step 3 using a spray gun of an air compressor, wherein the coating temperature is adjusted to a suitable temperature; after spraying, the temperature is kept warm to obtain double-layer membrane urea particles.

[0008] The present invention is also characterized in that: In step 1, the polyvinyl alcohols having a degree of polymerization of 2699 and 1799 are mixed in a mass ratio of 1:1.

[0009] In terms of weight, in step 1, there are 12 to 16 parts of polyvinyl alcohol, 4 to 8 parts of citric acid, 1 to 3 parts of corn stalk powder, and 200 parts of deionized water.

[0010] In step 1, the stirring speed is 750-850 r / min, and the stirring time is 15-25 min.

[0011] By weight, in step 2, there are 95 parts of anhydrous ethanol, 4-6 parts of ethyl cellulose, and 1-4 parts of glycerol.

[0012] The stirring time in step 2 is 15 to 25 minutes.

[0013] In step 3, the urea particle size is set to 3-4.5 mm; the coating pan angle is 45°; the insulation temperature after spraying is 55-75°C, and the insulation time is 5 min.

[0014] Step 3: preheating polishing temperature is 30~50℃, polishing time is 5~15min; keep warm for 2~8min after spraying; step 4: keep warm for 2~8min after spraying.

[0015] The second technical solution adopted by the present invention is: aqueous ester-coated urea fertilizer, aqueous ester-coated urea fertilizer prepared according to the above method.

[0016] The third technical solution adopted by the present invention is: application of water-based ester-coated urea fertilizer. When crops are planted, the water-based ester-coated urea fertilizer is applied to the soil at one time, and the nitrogen application rate is 50-150 mg / kg; the soil moisture content is maintained at 80-100% of the field water holding capacity.

[0017] Among the above raw materials in the present invention, citric acid has a multi-carboxyl structure, which can be esterified with the hydroxyl group on polyvinyl alcohol to form crosslinks inside the material. The occurrence of esterification and crosslinking can not only improve the water resistance of the material, but also improve its mechanical properties. At the same time, the carboxyl group on the citric acid can form a strong hydrogen bond with the hydroxyl group on the polyvinyl alcohol, increase the intermolecular interaction, and further improve the mechanical properties and thermal stability. The cellulose in the corn stalk contains a hydroxyl group that can form an intramolecular hydrogen bond with the hydroxyl group in the ester, thereby improving the water resistance and mechanical properties of the material. At the same time, the cheap and widely available corn stalk can serve as a coating structural material, which can reduce the coating cost and reduce the impact of improper straw treatment on the environment.

[0018] When glycerol is added to the ethyl cellulose ethanol solution, glycerol forms hydrogen bonds with the hydroxyl groups in the ethyl cellulose, which reduces the number of hydroxyl groups in the ethyl cellulose, thereby weakening and destroying the hydrogen bonds between molecules and within molecules, expanding the distance between molecules, improving the diffusion and mobility of the molecular chains, and making ethyl cellulose easier to process into coating materials. After ethyl cellulose is plasticized with glycerol, its hydrophobicity and sustained-release properties are improved.

[0019] The beneficial effects of the present invention are: 1. The present invention uses polyvinyl alcohol, citric acid and corn stalks which are widely available, environmentally friendly, cheap and easily available as raw materials. Using corn stalks as coating raw materials can improve the high added value utilization of corn stalks, reduce the preparation cost of coated fertilizers, and realize efficient and comprehensive utilization of resources.

[0020] 2. The present invention uses citric acid and corn stalks to mix with polyvinyl alcohol, which improves the mechanical properties, hydrophobic properties and thermal stability of the polyvinyl alcohol coating material. The mixture of polyvinyl alcohol with high polymerization degree and low polymerization degree can take into account the flexibility, strength and sustained release of the material.

[0021] 3. Ethyl cellulose plasticized with glycerol has enhanced hydrophobicity, stable mechanical structure and no biological toxicity. As the outer protective layer of coated fertilizer, it can effectively protect the fertilizer and significantly reduce the release rate of the fertilizer, thereby providing a continuous and balanced nutrient supply for crops. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a morphology structure diagram of the water-based ester-based cast film material of the present invention.

[0023] Figure 2 This is the infrared spectrum of the water-based ester-based cast film material of the present invention.

[0024] Figure 3 This is a cross-sectional morphology diagram of the water-based ester-coated urea fertilizer of the present invention. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention are described in detail below.

[0026] Example 1 This example is compared with the comparative example to clarify whether adding glycerol affects the performance of the external protective film. The specific preparation steps and formulation conditions are as follows: Put 95 parts of anhydrous ethanol into a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0027] 10 ml of the outer membrane solution was uniformly cast in a culture dish and placed in a biochemical incubator at 35° C. to dry and form a film. The treated outer membrane sustained-release film sheet was obtained, and the outer membrane performance test results are shown in Table 1.

[0028] Comparative Example 1-1 Put 95 parts of anhydrous ethanol into a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution, which is the outer membrane solution.

[0029] 10 ml of the outer membrane solution was uniformly cast in a culture dish and placed in a biochemical incubator at 35° C. to dry and form a film. The treated outer membrane sustained-release film sheet was obtained, and the outer membrane performance test results are shown in Table 1.

[0030] Table 1 Outer membrane material properties

[0031] As shown in Table 1 above, the outer film material in Example 1 has higher tensile strength and can more effectively protect the fertilizer. This shows that glycerol plays a role in enhancing the tensile strength in the preparation of the outer film (outer protective layer).

[0032] Example 2 This example is compared with the comparative example to clarify the effect of the lack of the outer protective layer on the performance of the coating material. The specific preparation steps and formulation conditions are as follows: (1) Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 70°C, 6 parts of citric acid are added, and the mixture is stirred at a constant temperature for 40 minutes. After the mixture is completely mixed, 2 parts of 80 mesh corn stalk powder are added and stirred at a constant temperature for 40 minutes to prepare the inner membrane solution.

[0033] (2) Place 95 parts of anhydrous ethanol in a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0034] 10 ml of the inner film solution was evenly cast in a culture dish and placed in a 35°C biochemical incubator to dry and form a film. Then 4 ml of the outer film solution was dripped on the surface of the inner film material to obtain a treated sustained-release film. The test results of the coating material performance are detailed in Table 2.

[0035] Comparative Example 2-1 Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) in a 150mL beaker, add 200 parts of deionized water, stir with a magnetic stirrer, and adjust the speed to about 800r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, cool it to 70°C, add 6 parts of citric acid, stir at a constant temperature for 40 minutes, and after it is completely mixed, finally add 2 parts of 80-mesh corn stalk powder and stir at a constant temperature for 40 minutes to prepare the inner membrane solution.

[0036] 10 ml of the inner film solution was uniformly cast in a culture dish, and placed in a 35°C biochemical incubator to dry and form a film, thereby obtaining a treated sustained-release film. The test results of the coating material performance are shown in Table 2.

[0037] Table 2 Coating material properties

[0038] The above Table 2 shows that the coating material prepared in Example 2 has higher tensile strength and better sustained-release performance because it contains an outer protective layer.

[0039] Example 3 This example is compared with the comparative example to clarify the influence of the ratio of inner film raw materials and reaction conditions on the performance of the coating material. The specific preparation steps and formulation conditions are as follows: (1) Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95 °C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 70 °C, 6 parts of citric acid are added, and the mixture is stirred at a constant temperature for 40 min. After the mixture is completely mixed, 2 parts of 80-mesh corn straw powder are added and stirred at a constant temperature for 40 min to prepare an inner membrane solution.

[0040] (2) Place 95 parts of anhydrous ethanol in a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0041] Take 10ml of the inner film solution and cast it evenly in a culture dish, and place it in a 35℃ biochemical incubator to dry it into a film. Then take 4ml of the outer film solution and drop it on the surface of the inner film material to obtain a treated slow-release film. The test results of the coating material performance are detailed in Table 3, and the test results of the coating material cumulative fertilizer penetration rate are detailed in Table 4.

[0042] Comparative Example 3-1 (1) Weigh 16 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 50°C, 4 parts of citric acid are added, and the mixture is stirred at a constant temperature for 40 minutes. After the mixture is completely mixed, 1 part of 80 mesh corn stalk powder is added and stirred at a constant temperature for 40 minutes to prepare the inner membrane solution.

[0043] (2) Place 95 parts of anhydrous ethanol in a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0044] Take 10ml of the inner film solution and cast it evenly in a culture dish, and place it in a 35℃ biochemical incubator to dry it into a film. Then take 4ml of the outer film solution and drop it on the surface of the inner film material to obtain a treated slow-release film. The test results of the coating material performance are detailed in Table 3, and the test results of the coating material cumulative fertilizer penetration rate are detailed in Table 4.

[0045] Comparative Example 3-2 (1) Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 50°C, 6 parts of citric acid are added, and the mixture is stirred at a constant temperature for 55 minutes. After the mixture is completely mixed, 3 parts of 80 mesh corn stalk powder are added and stirred at a constant temperature for 55 minutes to prepare the inner membrane solution.

[0046] (2) Place 95 parts of anhydrous ethanol in a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0047] Take 10ml of the inner film solution and cast it evenly in a culture dish, and place it in a 35℃ biochemical incubator to dry it into a film. Then take 4ml of the outer film solution and drop it on the surface of the inner film material to obtain a treated slow-release film. The test results of the coating material performance are detailed in Table 3, and the test results of the coating material cumulative fertilizer penetration rate are detailed in Table 4.

[0048] Comparative Example 3-3 (1) Weigh 12 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 50°C, 8 parts of citric acid are added, and the mixture is stirred at a constant temperature for 70 minutes. After the mixture is completely mixed, 2 parts of 80 mesh corn stalk powder are added and stirred at a constant temperature for 70 minutes to prepare the inner membrane solution.

[0049] (2) Place 95 parts of anhydrous ethanol in a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0050] Take 10ml of the inner film solution and cast it evenly in a culture dish, and place it in a 35℃ biochemical incubator to dry it into a film. Then take 4ml of the outer film solution and drop it on the surface of the inner film material to obtain a treated slow-release film. The test results of the coating material performance are detailed in Table 3, and the test results of the coating material cumulative fertilizer penetration rate are detailed in Table 4.

[0051] Table 3 Coating material properties

[0052] Table 4 Cumulative fertilizer penetration rate of coating materials

[0053] The above Tables 3-4 show that the coating material in Example 3 has higher tensile strength and stronger hydrophobicity than the coating material in the comparative example, is more conducive to isolating external moisture, and has better sustained-release effect, which proves that the inner membrane material formula and reaction conditions in Example 3 are optimal.

[0054] Example 4 This example is compared with the comparative example to clarify the influence of the ratio of outer film raw materials on the performance of the coating material. The specific preparation steps and formulation conditions are as follows: (1) Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 70°C, 6 parts of citric acid are added, and the mixture is stirred at a constant temperature for 40 minutes. After the mixture is completely mixed, 2 parts of 80 mesh corn stalk powder are added and stirred at a constant temperature for 40 minutes to prepare the inner membrane solution.

[0055] (2) Place 95 parts of anhydrous ethanol in a beaker, add 6 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0056] 10 ml of the inner film solution was evenly cast in a culture dish and placed in a 35°C biochemical incubator to dry and form a film. Then 4 ml of the outer film solution was dripped on the surface of the inner film material to obtain a treated sustained-release film. The test results of the coating material performance are detailed in Table 5.

[0057] Comparative Example 4-1 (1) Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 70°C, 6 parts of citric acid are added, and the mixture is stirred at a constant temperature for 40 minutes. After the mixture is completely mixed, 2 parts of 80 mesh corn stalk powder are added and stirred at a constant temperature for 40 minutes to prepare the inner membrane solution.

[0058] (2) Place 95 parts of anhydrous ethanol in a beaker, add 4 parts of ethyl cellulose, and stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 4 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0059] 10 ml of the inner film solution was evenly cast in a culture dish and placed in a 35°C biochemical incubator to dry and form a film. Then 4 ml of the outer film solution was dripped on the surface of the inner film material to obtain a treated sustained-release film. The test results of the coating material performance are detailed in Table 5.

[0060] Comparative Example 4-2 (1) Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, and stir with a magnetic stirrer at a speed of about 800 r / min. After the test begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 70°C, 6 parts of citric acid are added, and the mixture is stirred at a constant temperature for 40 minutes. After the mixture is completely mixed, 2 parts of 80 mesh corn stalk powder are added and stirred at a constant temperature for 40 minutes to prepare the inner membrane solution.

[0061] (2) Place 95 parts of anhydrous ethanol in a beaker, add 6 parts of ethyl cellulose, and stir manually with a glass rod. Stir at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 1 part of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0062] 10 ml of the inner film solution was evenly cast in a culture dish and placed in a 35°C biochemical incubator to dry and form a film. Then 4 ml of the outer film solution was dripped on the surface of the inner film material to obtain a treated sustained-release film. The test results of the coating material performance are detailed in Table 5.

[0063] Table 5 Coating material performance test

[0064] Table 5 above shows that the coating material in Example 4 has higher tensile strength, stronger hydrophobicity and better sustained-release effect than the coating material in the comparative example, which proves that the outer film material formula in Example 4 is optimal.

[0065] Example 5 This example is compared with the comparative example to clarify the influence of urea particle size and granulation temperature on the slow-release performance of fertilizer in the preparation of coated fertilizer. The specific preparation steps and formulation conditions are as follows: (1) Weigh 14 parts of polyvinyl alcohol with a degree of polymerization of 2699 and 1799 (mixed in a ratio of 1:1) into a 150 mL beaker, add 200 parts of deionized water, stir with a magnetic stirrer, and adjust the speed to about 800 r / min. After the experiment begins, the temperature of the magnetic stirrer is gradually adjusted to 95°C until the polyvinyl alcohol is completely dissolved. After the polyvinyl alcohol is completely dissolved, the temperature is lowered to 70°C, 6 parts of citric acid are added, and the mixture is stirred at a constant temperature for 40 minutes. After the mixture is completely mixed, 2 parts of 80 mesh corn stalk powder are finally added and stirred at a constant temperature for 40 minutes to prepare an inner membrane solution. 95 parts of anhydrous ethanol are placed in a beaker, and 6 parts of ethyl cellulose are added. Stir with a magnetic stirrer at room temperature for 15 to 25 minutes until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution. Add 2 parts of glycerol to the ethyl cellulose ethanol solution and stir at room temperature for 15 minutes to obtain an outer membrane solution.

[0066] (2) Place 100 portions of urea granules with a particle size of 4 to 4.5 mm in a water chestnut-type coating machine and preheat and polish at 40°C for 10 minutes. Then adjust the coating temperature to 65°C, and use a spray gun connected to an air compressor to spray the prepared inner film solution onto the surface of the urea granules to form a coating layer, with the coating pan angle being 45°. After spraying, keep the temperature at 65°C for 5 minutes. Take the prepared outer film solution and spray it again using the spray gun of the air compressor, with the coating temperature being 65°C and the coating pan angle being 45°. After spraying, keep the temperature at 65°C for 5 minutes.

[0067] The compressive strength results of the coated slow-release urea fertilizer prepared by the above method are shown in Table 6, and the urea dissolution rate results are shown in Table 7.

[0068] Comparative Example 5-1 (1) Same as step (1) of Example 5.

[0069] (2) Place 100 portions of urea granules with a particle size of 3 to 3.5 mm in a water chestnut-type coating machine and preheat and polish at 40°C for 10 minutes. Then adjust the coating temperature to 55°C, and use a spray gun connected to an air compressor to spray the prepared inner film solution onto the surface of the urea granules to form a coating layer, wherein the coating pan angle is 45°. After spraying, keep warm at 55°C for 5 minutes. Take the prepared outer film solution and use the spray gun of the air compressor to spray it for the second time, wherein the coating temperature is 55°C; the coating pan angle is 45°. After spraying, keep warm at 55°C for 5 minutes.

[0070] The compressive strength results of the coated slow-release urea fertilizer prepared by the above method are shown in Table 6, and the urea dissolution rate results are shown in Table 7.

[0071] Comparative Example 5-2 (1) Same as step (1) of Example 5.

[0072] (2) Place 100 portions of urea granules with a particle size of 3.5 to 4 mm in a water chestnut-type coating machine and preheat and polish at 40°C for 10 minutes. Then adjust the coating temperature to 75°C, and use a spray gun connected to an air compressor to spray the prepared inner film solution onto the surface of the urea granules to form a coating layer, with the coating pan angle being 45°. After spraying, keep the temperature at 75°C for 5 minutes. Take the prepared outer film solution and spray it again using the spray gun of the air compressor, with the coating temperature being 75°C and the coating pan angle being 45°. After spraying, keep the temperature at 75°C for 5 minutes.

[0073] The compressive strength results of the coated slow-release urea fertilizer prepared by the above method are shown in Table 6, and the urea dissolution rate results are shown in Table 7.

[0074] Comparative Example 5-3 Select ordinary urea with a particle size of 3.5 to 4 mm.

[0075] The compressive strength results of the above-selected ordinary urea are shown in Table 6, and the urea dissolution rate results are shown in Table 7.

[0076] Table 6 Compressive strength of fertilizers

[0077] Table 7 Dissolution rate of fertilizer urea

[0078] The above Tables 6-7 show that the coated slow-release fertilizer in Example 5 has better nutrient slow-release effect and better mechanical strength than the fertilizer in the comparative example, which proves that the slow-release and mechanical properties of urea after coating are significantly improved compared with conventional urea. It also proves that the urea granule size of 4 to 4.5 mm and the granulation temperature of 65°C in Example 5 are optimal.

[0079] Example 6 According to the formulation process and implementation steps described in Example 5, an aqueous ester-coated urea fertilizer was obtained and applied to lettuce planting. When planting, the aqueous ester-coated urea fertilizer was applied to the soil at one time, and the nitrogen application rate was 100 mg / kg. The soil moisture content was maintained at 80-100% of the field water holding capacity. The application effect of the slow-release fertilizer on lettuce is shown in Table 8.

[0080] Comparative Example 6-1 According to the method in Example 6, conventional urea with the same nitrogen application amount was added to the soil when the lettuce was planted, and the water content conditions were the same. Similarly, the physiological indicators related to the growth of the lettuce were measured regularly, and the application effects are shown in Table 8.

[0081] Table 8 Application effect of coated slow-release urea fertilizer on lettuce

[0082] Table 8 above shows that the lettuce grown better and had better quality when the aqueous ester-coated urea fertilizer of the present invention was applied than when ordinary urea was applied, which proves the promoting effect of the slow-release fertilizer on the growth of lettuce.

[0083] The present invention will be further analyzed below in conjunction with the accompanying drawings.

[0084] Depend on Figure 1 It can be seen that the surface of the water-based ester-based cast film prepared by the present invention is relatively uniform and dense, indicating that the components react completely and have good compatibility. No obvious cracks are generated on the surface, indicating that the double membrane structure can effectively block the nutrient diffusion channel, and the dense cross-linked structure can ensure the slow release performance of the fertilizer.

[0085] Depend on Figure 2 It can be seen that by comparing the spectra of the treated sustained-release film prepared in Example 3 with those of PVA, citric acid, and straw, the position of the maximum absorption peak has changed and the peak intensity of the same peak position has changed drastically, which indicates that the number of functional groups and the type of chemical bonds have changed after the combination of the raw materials. Compared with the single-component PVA, the sustained-release film material has a higher absorption peak at 1420 cm -1 -CH2 bond bending vibration peak at 1500cm -1 The C=C absorption peak of the sustained-release membrane material disappeared, indicating that citric acid and straw had successfully modified it. -1 A new signal peak was generated at 3300 cm, which indicated the C=O stretching signal. A new group was introduced into the generated polymer, indicating that citric acid and polyvinyl alcohol underwent an esterification reaction. -1 The nearby -OH stretching vibration peak shifted to a lower wave number after the reaction, which indicates that the film material of the water-based ester-coated urea fertilizer of the present invention produces more excited electrons in the atoms, significantly enhancing the absorption of infrared light, and at the same time, hydrogen bonds are formed between the active groups, which weakens the -OH bond and causes the -OH bond vibration frequency to decrease, which is a typical "red shift". In general, after the mixed modification of the multi-component materials, the hydrophobic properties of the obtained slow-release film are enhanced, which is conducive to the slow release of nutrients.

[0086] Depend on Figure 3 It can be observed that the cross-section of the coated urea fertilizer has a double-layer structure. The upper layer is a glycerol / ethyl cellulose composite layer, and the lower layer is a polyvinyl alcohol / citric acid / straw composite layer. The two films are tightly attached, and the internal structure of each film layer is densely cross-linked. The cross-section is relatively smooth, without obvious cracks or holes, which can ensure the continuous slow release of nutrients.

Claims

1. A method for preparing an aqueous ester-coated urea fertilizer, characterized in that: The specific steps are as follows: Step 1: Mix polyvinyl alcohol and deionized water, stir with a magnetic stirrer, and heat to 95° C. until the polyvinyl alcohol is completely dissolved; cool the polyvinyl alcohol solution, add citric acid, and stir at a constant temperature; after complete mixing, add corn stalk powder and stir to obtain an aqueous ester-based polymer solution, i.e., an inner membrane solution; Step 2: adding ethyl cellulose to anhydrous ethanol and stirring until the ethyl cellulose is completely dissolved to obtain an ethyl cellulose ethanol solution, and adding glycerol to the ethyl cellulose ethanol solution and stirring to obtain an outer membrane solution; Step 3: Place the urea granules in a water chestnut-type coating machine for preheating and polishing, then adjust the coating temperature to 55-75°C, use a spray gun connected to an air compressor to spray the prepared inner film solution onto the surface of the urea granules to form a coating layer, and keep the temperature after spraying to obtain single inner film coated urea granules; Step 4: Then, the outer membrane solution described in step 2 is sprayed twice on the surface of the single inner membrane coated urea particles described in step 3 using a spray gun of an air compressor, wherein the coating temperature is adjusted to a suitable temperature; after spraying, the temperature is kept warm to obtain double-layer membrane urea particles.

2. The method for preparing the aqueous ester-coated urea fertilizer according to claim 2, characterized in that: In step 1, the polyvinyl alcohols having a degree of polymerization of 2699 and 1799 are mixed in a mass ratio of 1:

1.

3. The method for preparing the aqueous ester-coated urea fertilizer according to claim 2, characterized in that: In terms of weight, in step 1, there are 12 to 16 parts of polyvinyl alcohol, 4 to 8 parts of citric acid, 1 to 3 parts of corn stalk powder, and 200 parts of deionized water.

4. The method for preparing the aqueous ester-coated urea fertilizer according to claim 2, characterized in that: In terms of parts by weight, the stirring speed in step 1 is 750-850 r / min, and the stirring time is 15-25 min.

5. The method for preparing the aqueous ester-coated urea fertilizer according to claim 2, characterized in that: By weight, in step 2, there are 95 parts of anhydrous ethanol, 4-6 parts of ethyl cellulose, and 1-4 parts of glycerol.

6. The method for preparing the aqueous ester-coated urea fertilizer according to claim 2, characterized in that: The stirring time in step 2 is 15 to 25 minutes.

7. The method for preparing the aqueous ester-coated urea fertilizer according to claim 2, characterized in that: The urea particle sizes in step 3 are set to 3-4.5 mm respectively; the coating pan angle is 45°; the insulation temperature after spraying is 55-75° C., and the insulation time is 5 min.

8. The method for preparing the aqueous ester-coated urea fertilizer according to claim 2, characterized in that: The preheating polishing temperature in step 3 is 30-50°C, and the polishing time is 5-15 minutes; after spraying, the temperature is kept warm for 2-8 minutes; after spraying in step 4, the temperature is kept warm for 2-8 minutes.

9. Aqueous ester-coated urea fertilizer prepared according to the method according to any one of claims 1 to 8.

10. Application of aqueous ester-coated urea fertilizer, characterized in that: When planting crops, apply water-based ester-coated urea fertilizer to the soil at one time, with a nitrogen application rate of 50~150mg / kg; the soil moisture content is maintained at 80~100% of the field water holding capacity.

Citation Information

Cited By

  • Novel environment-friendly double-layer composite coated slow-release nitrogen fertilizer as well as preparation method and application thereof

    CN118125879A